Pendidikan Kesehatan Mempengaruhi Persepsi Remaja dalam Merawat Organ Reproduksi - Arfiah, Arfiah (Jurusan Kebidanan Poltekkes Kemenkes Mamuju, 2021)
Care of the reproductive organs is an initial effort to maintain reproductive health. Performing treatment of the wrong reproductive organs can cause infectious diseases in the reproductive organs. Based on the results of interviews the researcher obtained from 10 students that the behavior in caring for reproductive organs is not too well known. The research aims to find out the effect of health education on reproductive organ at Grade VIII of SMPN 7 Palu.This was a quantitative research with pre experimental design using one group pretest posttest deign. The research population was 41 respondents selected using total sampling. The data were analyzed through Wicoxon test. The data analysis used univariate analysis which is for analyzing a distribution of frequency, percentage of each viable while bivariate analysis used inferentially to search for the health education effect on reproductive organ at Grade VIII of SMPN 7 Palu, where the result of p=0.00 < α=0.05. In conclusion, there is a significant effect of Health Education on Teenagers’ Perception in Caring Reproductive Organ at Grade VIII of SMPN 7 Palu. The suggestion is after conducting health education dealing with reproductive organ it is expected that they can form a well self-concept followed by a good behavior and for the health officers that they can provide education for the students in order that they can care it better.